Size and welfare costs of price differences across European countries - Christian Rühl (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Studies employing micro price data suggest that price dispersion is larger between regions in different countries than between regions in the same country. To investigate the strength of this border effect, deviations from the law of one price are used in most studies to provide statistical evidence on the effect of borders on price dispersion. I propose an alternative measure of the economic costs of borders which has an explicitwelfare-theoretic foundation. Employing a unique micro price data set from households in Belgium, Germany and the Netherlands I provide evidence on the economic importance of price differences for households. I find that price dispersion within countries has only small economic importance, but that price dispersion between Belgium andGermany (and Belgium and theNetherlands) has considerable economic importance.
Keywords: D12; F00; F40; 330